2011
DOI: 10.1016/j.cis.2010.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Micropollutant sorption to membrane polymers: A review of mechanisms for estrogens

Abstract: Organic micropollutants such as estrogens occur in water in increasing quantities from predominantly anthropogenic sources. In water such micropollutants partition not only to surfaces such as membrane polymers but also to any other natural or treatment related surfaces. Such interactions are often observed as sorption in treatment processes and this phenomenon is exploited in activated carbon filtration, for example. Sorption is important for polymeric materials and this is used for the concentration of such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
140
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 246 publications
(154 citation statements)
references
References 190 publications
4
140
0
6
Order By: Relevance
“…4 Adicionalmente, sugere-se que os grupos fenólicos, ricos em elétrons p, podem propiciar interações do tipo p-p com grupos fenil deficientes em elétrons dos materiais poliméricos. 5 Dentre os materiais testados, os únicos que poderiam ser utilizados para transferência das soluções de Estrona, Estradiol e Etinilestradiol do frasco de amostra para o cartucho de SPE são vidro e teflon, os quais permitiram recuperações médias entre 97 e 102% de todos os estrogênios em estudo, com desvios padrão relativos da ordem de 5%. Estes resultados são coerentes com os antecedentes relatados na literatura, 4 que sugerem o uso de teflon, em função da baixa adsorção apresentada em relação à estrona.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…4 Adicionalmente, sugere-se que os grupos fenólicos, ricos em elétrons p, podem propiciar interações do tipo p-p com grupos fenil deficientes em elétrons dos materiais poliméricos. 5 Dentre os materiais testados, os únicos que poderiam ser utilizados para transferência das soluções de Estrona, Estradiol e Etinilestradiol do frasco de amostra para o cartucho de SPE são vidro e teflon, os quais permitiram recuperações médias entre 97 e 102% de todos os estrogênios em estudo, com desvios padrão relativos da ordem de 5%. Estes resultados são coerentes com os antecedentes relatados na literatura, 4 que sugerem o uso de teflon, em função da baixa adsorção apresentada em relação à estrona.…”
Section: Resultsunclassified
“…Recentemente foram publicados três trabalhos que discutem o efeito da natureza dos meios filtrantes na recuperação de estrogênios, [4][5][6] o que demonstra a relevância da questão. No primeiro trabalho, 4 estrona foi utilizada como estrogênio modelo, observando-se significativa adsorção de matérias filtrantes constituídos de nylon, polipropileno, politetrafluoroetileno e acetato de celulose.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Jin et al [5] observed the impact of different organic matter types on micropollutant adsorption behaviour. Membrane material can also have a significant influence on adsorption [11]. For example, Jermann et al [12] observed up to 80% adsorption of estradiol to polyethersulfone ultrafiltration (UF) membranes compared to only 8% adsorption to regenerated cellulose UF membranes.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the chemical structures of CHCA and the methoxylated estrogens, adducts could form through π-π interactions between the aromatic ring of the estrogens and the phenyl group of CHCA, cation-π interactions between the aromatic ring of the estrogens and the cyano group of CHCA, or through general hydrogen bonding between the two compounds. 19 Although interactions between the analyte and CHCA are not very strong, the ions [M+H+CHCA] + were selected as precursor ions to produce specific fragments of isomeric 2-and 4-methoxylated estrogens. The devised method is the first report, demonstrating that methoxyestrogens can be detected by MALDI-MS as analyte-matrix adducts using CHCA as the matrix, which resulted in good selectivity through the movement of small molecules.…”
Section: Identification Of Methoxylated Estrogens By Maldi-msmentioning
confidence: 99%